Teachers’ Perceptions Of Using The Hinative App For Pronunciation Learning - Idris, Fahmi; Lubis, Yani (Jurnal Pendidikan, Sains Sosial, dan Agama, 2023)
This study looks at how English teachers in Binjai, Indonesia, use the HiNative app to help students learn pronunciation. This research looks at how HiNative can be used in the classroom. It looks at how well it works, what the benefits are, and what the problems might be. This is important because people are focusing more on being able to communicate well, and more and more tools are being used to help with learning languages. Four English teachers were interviewed and gave answers to a questionnaire. We used something called 'thematic analysis', following a method described by Braun and Clarke in 2006, to examine the teachers' experiences and insights. The results show that HiNative had a positive effect on student engagement, motivation, and their self-awareness of pronunciation. Teachers said the app was easy to use and could provide real feedback from native speakers. But there are also some problems, such as limited internet access, people having different levels of digital skills, and not being part of the school day. The study says that HiNative can be a useful tool to help with teaching pronunciation if there is enough training, the right infrastructure, and good teaching plans. These insights are important for the wider discussion about using mobile technology in teaching English as a second language. They show how ready teachers are to use mobile technology and how schools and other organisations support them.